The Students' Mathematical Literacy in Solving HOTS Problems: Does Learning Style Make a Difference? - Khan, Salfadhilla Najma; Setyaningsih, Rini (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Kerinci, 2024)
Differences in students' learning styles, whether visual, auditory, or kinesthetic, affect the way of students in absorbing, processing, and understanding the mathematical information provided. This statement indicates that differences in learning styles also affect students' mastery of mathematical literacy and students' skills in solving problems involving higher-order thinking skills. So, this study aims to describe students' mathematical literacy skills in solving higher-order thinking skills (HOTS)-oriented problems in terms of students' learning styles. The research used descriptive qualitative research that is involving 6 eighth-grade students at a junior high school in Blora, Central Java, Indonesia, as research subjects selected using simple random sampling techniques. The instruments used were a learning style questionnaire to identify students' learning styles, HOTS-oriented equation of a straight line problems to reveal students' mathematical literacy, and interviews to confirm the answers given by students in the test. Data were analyzed using an interactive model, namely data reduction, data presentation, and data verification, accompanied by triangulation techniques to ensure the validity of the data. The results showed that students with a visual learning style were more dominant in mastering communication skills and the ability to use language and symbolic, formal, and technical operations. In contrast, students with auditory learning styles are only dominant in mastering communication skills. While students with kinesthetic learning styles are more dominant in mastering language use skills and symbolic, formal, and technical operations.